2006
DOI: 10.1007/s00253-006-0390-x
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Bacillus thuringiensis GO33A with broad insecticidal activity against lepidopteran and coleopteran pests

Abstract: A recombinant plasmid pSTK-3A containing cry3Aa7 gene encoding a coleopteran-specific insecticidal protein was constructed and introduced into wild Bacillus thuringiensis subsp. aizawai G03, which contained cry1Aa, cry1Ac, cry1Ca, and cry2Ab genes and was highly toxic to lepidopteran insect pests. The genetically engineered strain were named G033A. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis and Western blot analysis demonstrated that the cry3Aa7 gene was expressed normally and produced a 67 kDa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 26 publications
1
49
0
Order By: Relevance
“…The bacterial strains and plasmids used in this study are listed in Table 1. E. coli JM110 was used for cloning, while SCS110 was used to produce nonmethylated plasmid DNA for B. thuringiensis transformation (45).…”
Section: Methodsmentioning
confidence: 99%
“…The bacterial strains and plasmids used in this study are listed in Table 1. E. coli JM110 was used for cloning, while SCS110 was used to produce nonmethylated plasmid DNA for B. thuringiensis transformation (45).…”
Section: Methodsmentioning
confidence: 99%
“…The bacterial strains and plasmids used in this study are listed in Table 1. Escherichia coli TG1 was used as the host for the cloning experiments, while SCS110 was used to generate unmethylated plasmid DNA for B. thuringiensis transformations (23,24). B. thuringiensis HD73 was used as the recipient strain to monitor promoter activity and clone the target gene (25,26).…”
Section: Methodsmentioning
confidence: 99%
“…Currently, the two major groups of plant derived genes used to confer insect resistance on crops are lectins and inhibitors of digestive enzymes (proteases and amylase inhibitors). Lectins have been introduced into crops genomes and are now being tested in field conditions Hilder et al, 1987;Hilder et al, 1999;Carlini et al, 2002;Schuler et al, 1998;Ranjeker et al, 2003;Schnepf & whitely, 1981;Smith & Boyko, 2006;Christou et al, 2006;Wang, 2006;Zhao, 2006;Ferry, 2006). Also, for the first time Jjanhong et al (2003) reported that transgenic tobacco expressing Pinellia ternata agglutinin (pta) gene induced enhance level of resistance to M. persicae.…”
Section: Transgenic Plants With Insecticidal Lectin Genementioning
confidence: 99%